Dependence of Potato Growth, Development, and Yield on Irrigation Methods in The Conditions of The Zarafshan Valley - Rizaev Sh.Kh.; Mirfozilov N.A.; Bobomirzaev P.Kh.; Sharifov K. (American Journal of Biology and Natural Sciences, 2026)
This article presents data on the dependence of potato growth, development, and yield on irrigation methods under the conditions of meadow-gray soils of the Zarafshan valley.